2002
DOI: 10.1046/j.1472-8206.2002.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Wine polyphenols modulate calcium handling in rat aorta: involvement of nitric oxide pathway

Abstract: The effects of short-term oral administration of red wine polyphenolic compounds (RWPCs) on blood pressure and vascular reactivity were investigated in rats. The consequence of RWPCs treatment on agonist-induced contractility of rat aorta with respect to Ca2+ handling was assessed, by examining both intracellular Ca2+ store and extracellular Ca2+ influx components of the response. Rats were treated daily for 7 days by intragastric administration of either 5% glucose, or RWPCs (20 mg/kg) [from two different sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…The present study does not identify the nature or origin of the changes in arterial stiffness induced by grapefruit flavanones. However, previous studies using different categories of flavonoids, including soy isoflavones and wine flavanols, have demonstrated their ability to modulate calcium handling in human and rat arteries (38,39). This effect is consistent with clinical data showing the action of flavonoids on arterial stiffness because this action is directly related to vascular tone, which is itself dependent on intracellular free calcium.…”
Section: Figuresupporting
confidence: 77%
“…The present study does not identify the nature or origin of the changes in arterial stiffness induced by grapefruit flavanones. However, previous studies using different categories of flavonoids, including soy isoflavones and wine flavanols, have demonstrated their ability to modulate calcium handling in human and rat arteries (38,39). This effect is consistent with clinical data showing the action of flavonoids on arterial stiffness because this action is directly related to vascular tone, which is itself dependent on intracellular free calcium.…”
Section: Figuresupporting
confidence: 77%
“…This effect could be related with previous reports that mangiferin inhibits crel and Rel-A which interact with intracellular Ca 2+ -loaded calmodulin [36]. Pholyphenols also show a strong capacity to modulate Ca 2+ levels [37].…”
Section: Discussionsupporting
confidence: 86%
“…For example, recent studies have identified a range of beneficial biological outcomes of oil palm phenolics (OPP) including antioxidant, antiinflammatory, anti-diabetic, neuro-protective as well as vascular protective qualities (Abeywardena et al, 2002;Bolsinger, Pronczuk, Sambanthamurthi, & Hayes, 2014;Leow, Sekaran, Sundram, Tan, & Sambanthamurthi, 2013a;Leow, Sekaran, Tan, Sundram, & Sambanthamurthi, 2013b;Nasef, Mehta, Murray, Marlow, & Ferguson, 2014;Sambanthamurthi et al, 2011). These observation for OPP are in agreement with several other plant extracts and isolated polyphenols and flavonoids reported to exert biological actions on various cardiac (Fang et al, 2011;Wallace, Baczko, Jones, Fercho, & Light, 2006;Wu, Loh, Cheng, Lu, & Lin, 2013) and vascular smooth muscle cell preparations including modulation of contractility (Diebolt & Andriantsitohaina, 2002;Protic et al, 2013;Zhu, Wang, Ou, Han, & Li, 2013). Several polyphenols exert their effects on contractility usually by modulation of ion channels (Protic et al, 2013;Tadano et al, 2010;Wu et al, 2013) and other important pathways linked to motility in health and disease (Abe et al, 2012).…”
Section: Introductionsupporting
confidence: 53%
“…It has been further demonstrated that forms of dietary resistant starch (RS), that result in the microbial generation of short chain fatty acids (SCFA), can modulate the contractility of the proximal colon (Bajka et al, 2010;Patten et al, 2015) and increase motility of the distal colon (Soret et al, 2010). Since plant polyphenols may also affect smooth muscle contractility (Diebolt & Andriantsitohaina, 2002), the aim of this study was to examine the effects of OPP in the diet on whole gut transit, colonic contractility and distal colonic motility of the rat compared to a source of RS, high amylose maize starch (HAMS), that like polyphenols, is resistant to upper gut digestion. Our hypothesis is that OPP will influence gut contractility and motility.…”
Section: Introductionmentioning
confidence: 99%